2019
DOI: 10.1001/jamaoncol.2019.0001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Taxane Plus Platinum Regimens vs Doxorubicin Plus Cisplatin as Adjuvant Chemotherapy for Endometrial Cancer at a High Risk of Progression

Abstract: for the Japanese Gynecologic Oncology Group IMPORTANCE The efficacy of taxane plus platinum regimens has been demonstrated for advanced or recurrent endometrial cancer; however, it has not been assessed in postoperative adjuvant chemotherapy for endometrial cancer.OBJECTIVE To evaluate the clinical benefit of taxane plus platinum compared with standard doxorubicin plus cisplatin as postoperative adjuvant chemotherapy in endometrial cancer. DESIGN, SETTING, AND PARTICIPANTSIn this multicenter, open-label, phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…The median number of LNs removed was 11 (range: 1-90) and 20 (range: 1-78) in the study by Chan et al and Polterauer et al, respectively [4,21]. In this study, we had a higher median number of LNs removed, [29][30][31][32][33][34][35][36][37] in the chemotherapy alone group and 25 (IQR: 18-39) in the chemoradiotherapy group. Due to the vast variability in the number of lymph nodes removed, it was unknown if the LNR cut-off values could be used to guide the choice of adjuvant therapy.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The median number of LNs removed was 11 (range: 1-90) and 20 (range: 1-78) in the study by Chan et al and Polterauer et al, respectively [4,21]. In this study, we had a higher median number of LNs removed, [29][30][31][32][33][34][35][36][37] in the chemotherapy alone group and 25 (IQR: 18-39) in the chemoradiotherapy group. Due to the vast variability in the number of lymph nodes removed, it was unknown if the LNR cut-off values could be used to guide the choice of adjuvant therapy.…”
Section: Discussionmentioning
confidence: 47%
“…Doxorubicin plus cisplatin or paclitaxel plus carboplatin was the most commonly used chemotherapy for patients with advanced-stage endometrial cancer in Taiwan [32]. Recently, a randomised trial revealed that the survival outcomes between these chemotherapy types were not different [33]. The number of patients that underwent radiotherapy alone was small in our cohort (n = 42); hence, these patients were excluded from this study.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the incidence and mortality rates of EC are expected to rise both in developed and developing countries with the increasing aging population and prevalence of obesity (32). Treatment for metastatic EC is ineffective and metastasis is the major reason for relapse and death, since there is no effective therapy for this condition (33). Therefore, identifying the molecular mechanisms of the peritoneal metastatic process is crucial for developing novel preventive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence showing poorer chemotherapy outcomes in cervical and uterine cancers than in ovarian cancer, TC therapy has been recommended for metastatic or recurrent cervical cancer. 3) On the other hand, doxorubicin (DXR) and CDDP combination therapy (AP therapy), docetaxel (DTX) and CBDCA combination therapy (DC therapy) or TC therapy has been recommended for uterine cancer. 4) CBDCA used in TC therapy is excreted predominantly by the kidneys, with approx.…”
Section: Introductionmentioning
confidence: 99%
“…3) On the other hand, doxorubicin (DXR) and CDDP combination therapy (AP therapy), docetaxel (DTX) and CBDCA combination therapy (DC therapy) or TC therapy has been recommended for uterine cancer. 4) CBDCA used in TC therapy is excreted predominantly by the kidneys, with approx. 70% being eliminated through urine.…”
Section: Introductionmentioning
confidence: 99%